-3(-7w+4)-3w=4(w-5)-4

Simple and best practice solution for -3(-7w+4)-3w=4(w-5)-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-7w+4)-3w=4(w-5)-4 equation:


Simplifying
-3(-7w + 4) + -3w = 4(w + -5) + -4

Reorder the terms:
-3(4 + -7w) + -3w = 4(w + -5) + -4
(4 * -3 + -7w * -3) + -3w = 4(w + -5) + -4
(-12 + 21w) + -3w = 4(w + -5) + -4

Combine like terms: 21w + -3w = 18w
-12 + 18w = 4(w + -5) + -4

Reorder the terms:
-12 + 18w = 4(-5 + w) + -4
-12 + 18w = (-5 * 4 + w * 4) + -4
-12 + 18w = (-20 + 4w) + -4

Reorder the terms:
-12 + 18w = -20 + -4 + 4w

Combine like terms: -20 + -4 = -24
-12 + 18w = -24 + 4w

Solving
-12 + 18w = -24 + 4w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-4w' to each side of the equation.
-12 + 18w + -4w = -24 + 4w + -4w

Combine like terms: 18w + -4w = 14w
-12 + 14w = -24 + 4w + -4w

Combine like terms: 4w + -4w = 0
-12 + 14w = -24 + 0
-12 + 14w = -24

Add '12' to each side of the equation.
-12 + 12 + 14w = -24 + 12

Combine like terms: -12 + 12 = 0
0 + 14w = -24 + 12
14w = -24 + 12

Combine like terms: -24 + 12 = -12
14w = -12

Divide each side by '14'.
w = -0.8571428571

Simplifying
w = -0.8571428571

See similar equations:

| W=1000-0.2t | | 28a^3b^4+20a^2b^2-16ab^3= | | x^8=140 | | 40x-40=28 | | 67+4y-30=15y-12-4y | | 9+3y-3=7y+15-3y | | 8x+3y=67 | | 8x-5y=-9 | | 18+-9= | | V(w-l)=p | | 93-(7x+6)=7(x+6)+x | | 2x^2+14x+59=0 | | Ab+c=2 | | 0=p-20/-2 | | 8x+9y-(2x+y)= | | log(x)+8.75=0 | | -2(6x-7)+6x=5+2(2x-3) | | j+16=-10-j | | 20sinx=10 | | 10x+9-9x-15= | | 4n-40=7(-2nt+2) | | 4/100= | | 4/109= | | 7/8=-2/3x-5 | | (2x-3)+(x+7)=42 | | -2=d-17/-1 | | 2x+3=112 | | 5a-3a=45-9 | | 25x-60=115 | | q^2+2g=323 | | 3x-20=1x | | 4v+8=26-2y |

Equations solver categories